Планування процесів забезпечення якості у великих та географічно розподілених гібридних IT–проектах - Муравецький, Святослав Аркадійович; Крамський, Сергій Олександрович (НТУ "ХПІ", 2016)
Розкрито особливості операційно-проектної діяльності у великих, географічно розподілених ІТ-проектах. Надано структуру процесів з забезпечення контролю якості кінцевого продукту. Розглянуті сучасні методи інтеграції процесів тестування у процеси розробки програмного забезпечення. Розглянуті групи існуючих моделей планування та розробки програмних продуктів. Надана стисла характеристика процесів контролю якості у кожній групі. Надані рекомендації з адаптації належних процесів контролю якості у гібридному проекті.

There have been discussed key points of operational activates in a large scale geographically spread software development projects. A look taken at required QA processes structure in such project. There have been given up to date methods of integration quality assurance processes into software development processes. There have been reviewed existing groups of software development methodologies. Such as sequential, agile and based on RPINCE2. There have been given a condensed overview of quality assurance processes in each group. There have been given a review of common challenges that sequential and agile models are having in case of large geographically spread hybrid software development project. A recommendations were given in order to tackle those challenges. The conclusions about the best methodology choice and appliance to particular project have been made.
Planning Quality Assurance processes in a large scale geographically spread hybrid software development project
Keywords: забезпечення програмне; діяльність операційно-проектна; продукт; контроль якості; software development; methodology; operational